(untitled) (Editora Impacto Científico, 2025)
This study analyzed the importance of hygienic-sanitary control in food distribution within Food and Nutrition Units (FNUs), a crucial step for preventing Foodborne Diseases (FBDs). Distribution is a Critical Control Point (CCP), where the main risk is microbial multiplication due to food exposure in the temperature "danger zone" 5ºC e 60ºC. Control requires maintaining hot foods above 60ºC and cold foods below 5ºC, according to ANVISA’s RDC 216/2004. Studies in hospital FNUs indicate that, even in units with good overall compliance, punctual failures in Good Practices (BP) persist, such as in hand hygiene of handlers, and infrastructural deficiencies that compromise safety. It is concluded that the Nutritionist is responsible for monitoring the time/temperature factor, using checklists to inspect the structure, and training the team, ensuring that food reaches the consumer in ideal sanitary conditions, which is vital for public health and patient recovery. DOI: https://doi.org/10.56238/edimpacto2025.090-033